TEOA Promotes Autophagic Cell Death via ROS-Mediated Inhibition of mTOR/p70S6k Signaling Pathway in Pancreatic Cancer Cells - Yang, Chen; Li, Yanchun; Hu, Wanye; Wang, Xu; Hu, Jiayu; Yuan, Chen; Zhou, Chaoting; Wang, Hairui; Du, Jing; Wang, Ying; Tong, Xiangmin (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic cancer is a common malignant tumor with high mortality, and novel therapeutic options have focused on ameliorating its poor prognosis. TEOA, a traditional Chinese herbal medicine, exhibits anti-inflammatory and anti-cancer activities. Our recent study has shown that TEOA inhibits proliferation and induces DNA damage in diffuse large B-cell lymphoma cells by activating the ROS-mediated p38 MAPK pathway. However, its effects on pancreatic cancer cells remain unknown. In the present study, we evaluated the effects of TEOA on the proliferation, migration, and invasion of pancreatic cancer cells and explored the possible underlying mechanism of action. We found that TEOA significantly inhibited the proliferation, invasion, and migration of pancreatic cancer cells in a time- and dose-dependent manner. Mechanistically, TEOA significantly induced mitochondrial dysfunction in PANC1 and SW1990 cells, as evidenced by the collapse of the mitochondrial membrane potential, exhausted ATP level, and excessive accumulation of intracellular ROS. Notably, our further experiments showed that TEOA induced autophagic cell death in pancreatic ductal adenocarcinoma cells by inactivating the ROS-dependent mTOR/p70S6k signaling pathway. More importantly, both pharmacological or genetic blocking of the autophagic flux signal could partly restore the cytotoxicity of TEOA, whereas activation of autophagy by rapamycin or starvation in EBSS buffer facilitated the cytotoxicity of TEOA. Concomitantly, N-acetylcysteine, a ROS scavenger, abolished the inhibition of the mTOR signaling pathway, thus preventing autophagy and restoring cell viability. Taken together, our results reveal that TEOA can lead to ROS-dependent autophagic cell death of pancreatic cancer cells by inducing mitochondrial dysfunction, which might be a promising therapeutic agent for pancreatic cancer.